Direct Collapse Accretion Disks within Dark Matter Halos: Saturation of the Magnetorotational Instability and the Field Expulsion - Yang Luo; Isaac Shlosman (The Astrophysical Journal)
We have used high-resolution zoom-in simulations of direct collapse to supermassive black hole (SMBH) seeds within dark mater halos in the presence of magnetic fields generated during the collapse, down to 10 ^−5 pc or 2 au. We confirm an efficient amplification of magnetic field during collapse, the formation of a geometrically thick self-gravitating accretion disk inside 0.1 pc, and damping of fragmentation in the disk by the field. This disk differs profoundly from SMBH accretion disks. We find the following: (1) The accretion disk is subject to the magnetorotational instability, which further amplifies the field to near equipartition. No artificial seeding of the disk field has been used. (2) The equipartition toroidal field changes its polarity in the midplane. (3) The nonlinear Parker instability develops, accompanied by the vertical buckling of the field lines, which injects material above the disk, leading to an increase in the disk scale height. (4) With the Coriolis force producing a coherent helicity above the disk, the vertical poloidal field has been generated and amplified. (5) We estimate that the associated outflow will be most probably squashed by accretion. The resulting configuration consists of a magnetized disk with β ≳ 0.1 and its magnetosphere with β ≪ 1, where β = P _th / P _B is the ratio of thermal to magnetic energy density. (6) The disk is highly variable, due to feeding by variable accretion flow, and strong vortical motions are present. (7) Finally, the negative gradient of the total vertical stress drives an equatorial outflow sandwiched by an inward accretion flow.